Pelaksanaan Yurisprudensi Hukum Waris Adat Masyarakat di Indonesia - Mozarto Omar Vivaldi Hermanto; Achmad Farhan Aly (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Inheritance law contains regulations that include the need to understand the dynamics and challenges in the property inheritance system, involving legal, cultural and social aspects. Jurisprudence reflects efforts to maintain a balance between local wisdom, justice and legal certainty in the inheritance of traditional property. This research uses a normative juridical method with a case approach, analyzing court decisions that have permanent legal force. Although the patrilineal customary inheritance system still applies in several regions of Indonesia, the view that customary inheritance law is irrelevant reflects the complexity of social and legal transformation. Although there are arguments that customary inheritance law does not always comply with justice and changing times, some judges in Indonesia still use jurisprudence or other inheritance laws in their decisions.